MODELING OF THE PROCESS OF COLLECTION, SORTING AND TRANSPORTATION OF LOGGING RESIDUES AT THE LOGGING AREA - Мохирев, Александр; Zyrjanov, Mihail; Medvedev, Sergey; Rjabova, Tatiana (Journal of Applied Engineering Science, 2020)
Effectiveness of economic development of logging industry is impossible without scientifically grounded strategies of formation of perspective technological logging processes with complex use of the total biomass of harvested trees. Degree of utilization of wood biomass is to be considered the most important principle of progressive logging technology. One of the main tasks of the national logging complex is the use of low-grade wood, lumpy wood waste, top of trees, twigs and branches, which will significantly improve efficiency of logging. To solve this problem, this article reviews the process of modeling of work of sorting and transportation machine designed for loading, sorting and transportation of felling residues to timber road. The technological scheme also provides cutting waste with knife for sorting by size. The study provides a detailed technological scheme of logging operations using forwarders with a removable body for loading, sorting and transportation of felling residues. The body of the forwarder is divided into compartments for transportation of waste with different parameters. The information and logical model of the process of collection, sorting and transportation of felling residue, which is proposed by machine, was offered. The formula for calculating the performance of operation of the sorting and transportation machine was obtained. Sorting according to species and types of felling residues is necessary for the production of fuel and technological wood chips for further use in production of valuable commercial products.